Impact of hypertension on left ventricular function in patients after anthracycline chemotherapy for malignant lymphoma. (15th January 2021) - Tanaka, Yusuke; Tanaka, Hidekazu; Hatazawa, Keiko; Yamashita, Kentaro; Sumimoto, Keiko; Shono, Ayu; Suzuki, Makiko; Yokota, Shun; Suto, Makiko; Mukai, Jun; Takada, Hiroki; Matsumoto, Kensuke; et al.
Abstract: Background: Hypertension is considered an important risk factors for cancer therapeutics-related cardiac dysfunction (CTRCD) as well as heart failure. However, the impact of hypertension and left ventricular (LV) hypertrophy (LVH), which is associated with hypertension, on LV function in patients treated with anthracycline chemotherapy for malignant lymphoma remains uncertain. Method: We studied 92 patients with malignant lymphoma and with preserved LV ejection fraction (LVEF). Echocardiography was performed before and two-month after anthracycline chemotherapy. CTRCD was defined as the presence of an absolute decrease in LVEF ≥10% to a final value <53%. LVH was defined as concentric hypertrophy, which was determined as relative wall thickness ≥ 0.42 and LV mass index >95 g/m 2 for females and > 115 g/m 2 for males. Results: Relative decrease in LVEF after anthracycline chemotherapy in patients with hypertension ( n  = 23) was significantly higher than that in patients without hypertension ( n  = 69) (−5.8% [−9.4, −1.3]) vs. (−1.1% [−4.1, 2.5]); P  = .005). Moreover, the prevalence of CTRCD in patients with hypertension tended to be higher than in those without hypertension (17% vs. 5%, p  = .09). A sequential logistic model for predicting CTRCD, based on baseline clinical variables including major clinical risk factors, was improved by the addition of the complication of hypertension ( P  = .049), and further improved by the addition of the presence of LVH ( P  = .023). Conclusions: Hypertension, especially when complicated by LVH, was found to be associated with LV dysfunction after anthracycline chemotherapy in patients with malignant lymphoma and preserved LVEF. Watchful observation or early therapeutic intervention may thus be needed for such patients by the addition of the presence of LVH. Highlights: Hypertension is considered an important risk factor for CTRCD as well as HF. Hypertension with LVH was strongly associated with CTRCD. Watchful observation may be needed for patients with hypertension and LVH.